(untitled) - Hoft, Hartmut F. W. (San Diego, California, 1998)
This book is interactive courseware designed to teach how to use Mathematica efficiently for solving problems arising in their major fields of study, such as mathematics, computer science, physics, or engineering
Keywords: Mathematica ( computer file ),Mathematica ( computer program language ),Mathematics; Data processing